Production of biodiesel from jatropha curcas L using sodium hydroxide and amano lipase M catalyst in an airlift reactor - Noorliana, Mohd Dahari (2010)
Currently there is an urgent need of develop alternative energy resources, such as biodiesel fuel due to the gradual reduction of world petroleum reserves and the impact of environmental pollution of increasing exhaust emissions. Based on the research before, the percentages of Biodiesel yield from J.Curcas L. is too low (30% yield). So, in this research the improvement of the production yield of biodiesel from J.Curcas L is done using Sodium hydroxide (NaOH) and Amano M. lipase in an airlift reactor. Biodiesel is a monoalkyl esters of long chain fatty acids derived from vegetable oils or animal fats by the transesterification with alcohols in the present of catalyst. The objective of this research is to investigate the best parameter of methanol to oil ratio, reaction time and temperature to produce high yield of biodiesel. Multiple step acid-base catalyzed transesteriﬁcation and enzymatic transesterification process using airlift reactor are the methods used in this research. The concentration of sodium hydroxide (NaOH) and sulphuric acid (H2SO) used are 1.5% (w/w), meanwhile the enzyme catalyst (Amano M lipase) used is 1 g. The methyl ester are analyze using GC/FID with the standard concentration of 0.004, 0.008,0.012, 0.016, 0.020 mg/mL. In this research, the optimal yield of biodiesel from jatropha oil at optimal sodium hydroxide catalyst concentration 1.5% (w/w), reaction temperature 50°C, reaction time one hour and molar ratio of methanol to oil 6:1. While the optimal yield of biodiesel from jatropha oil with Amano M. lipase enzyme is at temperature 35°C, reaction time 24 hour and molar ratio of methanol to oil 3:1. The enzymatic take long time of reaction but the quality of the biodiesel is more higher compare to the acid-base transesterification. Alcohol to oil ratio, reaction time, reaction temperature, and catalyst concentration are four primary factors affecting the yield of biodiesel.